Poly(ester amide)-Poly(ethylene oxide) Graft Copolymers: Towards Micellar Drug Delivery Vehicles - Gregory J. Zilinskas; Abdolrasoul Soleimani; Elizabeth R. Gillies (International Journal of Polymer Science)
Micelles formed from amphiphilic copolymers are promising materials for the delivery of drug molecules, potentially leading to enhanced biological properties and efficacy. In this work, new poly(ester amide)-poly(ethylene oxide) (PEA-PEO) graft copolymers were synthesized and their assembly into micelles in aqueous solution was investigated. It was possible to tune the sizes of the micelles by varying the PEO content of the polymers and the method of micelle preparation. Under optimized conditions, it was possible to obtain micelles with diameters less than 100 nm as measured by dynamic light scattering and transmission electron microscopy. These micelles were demonstrated to encapsulate and release a model drug, Nile Red, and were nontoxic to HeLa cells as measured by an MTT assay. Overall, the properties of these micelles suggest that they are promising new materials for drug delivery systems.